A hollow porous concentration gradient positive electrode material and a preparation method thereof

By adopting a hollow porous concentration gradient structure in the positive electrode material of lithium-ion battery, the difficulty of improving the performance of high-nickel positive electrode material is solved, the stability and circulation performance of the material are significantly improved, and the overall performance of lithium-ion batteries is enhanced.

CN114649521BActive Publication Date: 2025-01-03NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210331422.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-30
Publication Date
2025-01-03
Estimated Expiration
2042-03-30

AI Technical Summary

Technical Problem

The rate performance and circulation performance of high-nickel cathode materials still have room for improvement, and their cycle stability and safety performance are low, making it difficult to meet the needs of new energy vehicles.

Method used

Using hollow porous concentration gradient positive electrode material, the concentration gradient of metal nickel cobalt manganese ions is changed in the reactor, and the co-precipitation reaction is carried out under the action of complexing agent and precipitant to form a concentration gradient precursor, and sintering is carried out through two steps. The process forms an internal hollow porous structure to improve the stability of the material.

Benefits of technology

It significantly improves the stability and cycling performance of the positive electrode material, enhances the cycling and safety performance of lithium-ion batteries, shortens the diffusion distance of Li ions, and buffers the volume expansion and contraction caused by repeated deintercalation of Li ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114649521B_ABST
    Figure CN114649521B_ABST
Patent Text Reader

Abstract

The invention discloses a hollow porous type concentration gradient positive electrode material, wherein the concentrations of nickel ions, cobalt ions and manganese ions contained in the positive electrode material are distributed in a gradient from the center to the surface, and the concentration gradient of nickel ions contained in the positive electrode material decreases from the center of the positive electrode material to the surface of the positive electrode material, and the concentration of nickel ions located at the center of the positive electrode material is 90%-100%, and the concentration of nickel ions located at the surface of the positive electrode material is 60%-70%; the concentration gradients of cobalt ions and manganese ions contained in the positive electrode material both increase from the center of the positive electrode material to the surface of the positive electrode material, and the concentrations of cobalt ions and manganese ions located at the center of the positive electrode material are 0%-5%, and the concentrations of cobalt ions and manganese ions located at the surface of the positive electrode material are 15%-20%. The beneficial effects of the invention are as follows: the hollow porous type concentration gradient positive electrode material of the invention has a concentration gradient structure, has a higher material surface structure stability, and has obvious advantages in terms of cycle performance, rate and safety performance compared with ordinary homogeneous high nickel positive electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a hollow porous concentration gradient positive electrode material and a preparation method thereof. Background Art

[0002] At present, energy shortage has become a global problem. The energy sources that can be used include solar energy, hydrogen fuel, wind energy, etc. Among them, the most popular and widely used are lithium-ion batteries. In recent years, the new energy vehicle industry has developed rapidly. Among them, high-nickel ternary lithium battery electric vehicles with long driving range have developed more rapidly and become the main force in the market. Although the increase in Ni content will increase the specific capacity of the positive electrode material, it will also cause the material's cycle stability and safety performance to decrease. At present, the rate performance and cycle performance of high-nickel positive electrode materials still have a lot of room for improvement, which has become the focus and difficulty of research. Summary of the invention

[0003] The main purpose of the present application is to provide a hollow porous concentration gradient positive electrode material which is hollow and porous inside and can significantly improve the stability of the positive electrode material and a preparation method thereof.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] A hollow porous concentration gradient positive electrode material, wherein the concentrations of nickel ions, cobalt ions and manganese ions contained in the positive electrode material are distributed in a gradient from the center to the surface, the concentration gradient of the nickel ions contained in the positive electrode material decreases from the center to the surface of the positive electrode material, the concentration of the nickel ions located in the center of the positive electrode material is 90%-100%, and the concentration of the nickel ions located on the surface of the positive electrode material is 60%-70%; the concentration gradients of the cobalt ions and manganese ions contained in the positive electrode material both increase from the center to the surface of the positive electrode material, the concentrations of the cobalt ions and manganese ions located in the center of the positive electrode material are 0%-5%, and the concentrations of the cobalt ions and manganese ions located on the surface of the positive electrode material are 15%-20%.

[0006] By changing the concentration of nickel, cobalt and manganese ions flowing into the reactor, a coprecipitation reaction occurs under the action of a complexing agent and a precipitant to produce a concentration gradient precursor. Then, through a two-step sintering process, the metal ions diffuse from the high-concentration area to the low-concentration area, forming a positive electrode material with a hollow and porous interior. This special structure of the positive electrode material can significantly improve the stability of the positive electrode material, thereby improving the cycle performance of the lithium-ion battery prepared from it.

[0007] In the above-mentioned hollow porous concentration gradient positive electrode material, as a preferred embodiment, the acid radical ions of the nickel ions, cobalt ions and manganese ions are sulfate ions, nitrate ions, acetate ions or chlorate ions.

[0008] In a second aspect of the present application, a method for preparing a positive electrode material is provided, comprising the following steps:

[0009] (1) preparing a metal salt solution: preparing a salt solution A containing nickel, and / or cobalt, and / or manganese metal ions, wherein the molar ratio of nickel ion, cobalt ion, and manganese ion is (100-90):(0-5):(0-5); preparing a salt solution B containing nickel, cobalt, and manganese metal ions, wherein the molar ratio of nickel ion, cobalt ion, and manganese ion is (60-70):(20-15):(20-15);

[0010] (2) preparing a precipitant solution and a complexing agent solution;

[0011] (3) passing the solution B described in step (1) into solution A, and then passing the mixture of solution B and solution A into a reactor filled with deionized water, and at the same time passing a precipitant solution and a complexing agent solution into the reactor, and performing a coprecipitation reaction under inert conditions to obtain a nickel cobalt manganese hydroxide precipitate;

[0012] (4) The nickel-cobalt-manganese hydroxide precipitate obtained in step (3) is washed and dried in sequence to obtain a hydroxide precursor, which is then evenly mixed with a lithium salt and sintered to obtain a hollow porous concentration gradient positive electrode material.

[0013] The above-mentioned method for preparing a positive electrode material is a preferred embodiment. In step (1), the sum of the molar concentrations of metal ions in salt solution A and salt solution B is 1.3 mol / L-1.8 mol / L; and the acid ions in salt solution A and salt solution B are sulfate ions, nitrate ions, acetate ions or chlorate ions.

[0014] The above-mentioned method for preparing a positive electrode material, as a preferred embodiment, the concentration of the precipitant is 5 mol / L, and the precipitant is NaOH, KOH, Na2CO3, NaHCO3, K2CO3 or KHCO3; the concentration of the complexing agent is 10 g / L, and the complexing agent is ammonia water, ammonium bicarbonate, ammonium carbonate or ammonium oxalate.

[0015] The above-mentioned method for preparing a positive electrode material, as a preferred embodiment, the rate at which the mixed solution of solution B and solution A is passed into the reactor is twice the rate at which solution B is passed into solution A; preferably, the rate at which solution B is passed into solution A is 10-50 mL / min, the rate at which the mixed solution of solution B and solution A is passed into the reactor is 20-100 mL / min, the rate at which the precipitant solution is passed into the reactor is 5-30 mL / min, and the rate at which the complexing agent solution is passed into the reactor is 1-10 mL / min.

[0016] The above-mentioned method for preparing a positive electrode material is a preferred embodiment. In step (3), the inert condition is to fill the reactor with inert gas nitrogen; the temperature of the coprecipitation reaction is 20-70°C, the pH is 7.0-11.0, the stirring speed is 300-2000r / min, and the reaction time under these conditions is 20-100h.

[0017] As a preferred embodiment of the above method for preparing a positive electrode material, in step (4), the cleaning is: firstly rinse with alkaline solution at a temperature of 50-90°C, and then rinse with deionized water.

[0018] As a preferred embodiment of the above-mentioned method for preparing a positive electrode material, in step (4), the lithium salt is at least one of lithium hydroxide, lithium carbonate, lithium nitrate, and lithium acetate, and the molar ratio of the hydroxide precursor to the lithium salt is 1:1-1.2.

[0019] The above-mentioned method for preparing a positive electrode material is a preferred embodiment. In step (4), the sintering is as follows: first, heating to 500°C at a heating rate of 1 to 10°C / min, and keeping warm for 2 to 10 hours; then heating to 600°C at a heating rate of 1 to 10°C / min, and keeping warm for 1 to 2 hours; then heating to 800°C at a heating rate of 1 to 10°C / min, and keeping warm for 1 to 20 hours, and then cooling to room temperature with the furnace; then heating to 300°C at a heating rate of 1 to 10°C / min, and keeping warm for 1 to 15 hours, and finally cooling to room temperature with the furnace to obtain a hollow porous concentration gradient positive electrode material.

[0020] The beneficial effects of the present invention are as follows: the hollow porous concentration gradient positive electrode material of the present invention has a concentration gradient structure and has higher material surface structure stability. Compared with ordinary homogeneous high-nickel positive electrode materials, it has obvious advantages in terms of cycle performance, rate and safety performance.

[0021] During the preparation process of the hollow porous concentration gradient positive electrode material of the present invention, the nickel ion concentration at the center of the concentration gradient material is relatively high. During the sintering process, a porous hollow structure can be formed by the diffusion of metal ions. This structure increases the effective contact area, is conducive to the penetration of the electrolyte into the electrode material, shortens the diffusion distance of Li ions, and can also effectively buffer the volume expansion and contraction caused by repeated insertion and extraction of Li ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a flow chart of the process of preparing the positive electrode material of the present invention, in which the salt solution B flows into the salt solution A, and the mixed solution of the salt solution A and the salt solution B flows into the reaction kettle;

[0023] Figure 2This is a scanning diagram of element distribution of the cross section of the hydroxide precursor described in Example 1 tested by EPMA;

[0024] Figure 3 This is the SEM image of the positive electrode material described in Example 1 of the present invention;

[0025] Figure 4 This is the SEM image of the positive electrode material described in Example 2 of the present invention;

[0026] Figure 5 This is the SEM image of the positive electrode material described in Example 3 of the present invention;

[0027] Figure 6 This is the SEM image of the positive electrode material described in Example 4 of the present invention;

[0028] Figure 7 This is the SEM image of the positive electrode material described in Example 5 of the present invention;

[0029] Figure 8 This is the SEM image of the positive electrode material described in Comparative Example 1 of the present invention;

[0030] Fig. 9 This is the SEM image of the positive electrode material described in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be described clearly and completely in combination with examples. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.

[0032] The present invention changes the concentration of metal nickel, cobalt and manganese ions flowing into the reaction kettle, and a coprecipitation reaction occurs under the action of a complexing agent and a precipitating agent to obtain a concentration gradient precursor. The nickel concentration inside the concentration gradient precursor gradually decreases from 90% to 100% in the center to 60% to 70% on the surface, while the cobalt and manganese concentrations gradually increase from 0% to 5% in the center to 15% to 20% on the surface. Then, through a two-step sintering process, the metal ions diffuse from the high-concentration area to the low-concentration area, forming an internal hollow and porous positive electrode material. This special structure of the positive electrode material can significantly improve the stability of the positive electrode material, thereby improving the cycle performance of the lithium ion battery prepared therefrom.

[0033] Example 1

[0034] The method for preparing the hollow porous concentration gradient positive electrode material described in Example 1 comprises the following steps:

[0035] (1) Sulfate solution A and sulfate solution B are prepared, wherein the molar ratio of nickel ion, cobalt ion and manganese ion in salt solution A is 90:5:5, and the sum of the molar concentrations of nickel ion, cobalt ion and manganese ion in salt solution A is 1.3 mol / L; the molar ratio of nickel ion, cobalt ion and manganese ion in salt solution B is 60:20:20, and the sum of the molar concentrations of nickel ion, cobalt ion and manganese ion in salt solution B is 1.3 mol / L.

[0036] (2) preparing a precipitant sodium hydroxide solution and a complexing agent ammonia water respectively, wherein the concentration of the sodium hydroxide aqueous solution is 5 mol / L, and the concentration of the ammonia aqueous solution is 10 g / L;

[0037] (3) A reactor filled with deionized water was heated with a thermostatic water tank to make the temperature of the solution in the reactor reach 65°C and kept constant, 100L of salt solution A was added to the reactor filled with deionized water at a rate of 50mL / min, and 100L of salt solution B was added to salt solution A at a rate of 25mL / min, and sodium hydroxide aqueous solution and ammonia aqueous solution were added to the reactor at a rate of 30mL / min and 2mL / min, respectively, for coprecipitation reaction; nitrogen gas was introduced as protective gas, and the flow rate of the sodium hydroxide aqueous solution was adjusted to control the pH value of the reaction solution to 10.9, the concentration of ammonia in the solution to 3.0g / L, the stirring rate to 1000r / min, and the nitrogen flow rate to 0.3m 3 / h, react under this condition for 80h, and finally obtain nickel cobalt manganese hydroxide precipitate;

[0038] (4) The obtained nickel-cobalt-manganese hydroxide precipitate was washed twice with hot alkali solution at a temperature of 70° C., then washed four times with deionized water, and dried at a temperature of 120° C. for 15 h to obtain a hydroxide precursor. The element distribution of the cross section of the hydroxide precursor was tested by EPMA. Figure 2 . ( Figure 2 From left to right are Ni, Co and Mn. Figure 2 It can be seen that the concentration distribution of Ni element in nickel cobalt manganese hydroxide precipitate B gradually decreases from the center to the surface, while the concentration distribution of Co and Mn elements gradually increases from the center to the surface, and the three elements Ni, Co and Mn show a clear concentration gradient distribution. The ternary positive electrode material obtained by sintering the precursor with this concentration gradient structure has significantly improved cycle performance and thermal stability compared with the ordinary homogeneous high-nickel positive electrode material).

[0039] (5) The hydroxide precursor and lithium hydroxide are mixed evenly at a molar ratio of 1:1.04 and then sintered in a muffle furnace in two stages, and sufficient oxygen atmosphere is maintained during the sintering process. The three-stage sintering includes: heating from room temperature to 500°C at a heating rate of 2°C / min, keeping the temperature for 2 hours, then heating to 600°C at a heating rate of 2°C / min and keeping the temperature for 6 hours, then heating to 800°C at a heating rate of 2°C / min and keeping the temperature for 12 hours, then stopping heating and cooling to room temperature with the furnace; then heating to 300°C at a heating rate of 2°C / min and keeping the temperature for 10 hours, finally stopping heating and cooling to room temperature with the furnace, and obtaining a hollow porous concentration gradient positive electrode material.

[0040] Example 2

[0041] The method for preparing the hollow porous concentration gradient positive electrode material described in Example 2 comprises the following steps:

[0042] (1) preparing nitrate solution A and nitrate solution B, wherein the molar ratio of nickel ion, cobalt ion and manganese ion in salt solution A is 100:0:0, and the sum of the molar concentrations of nickel ion, cobalt ion and manganese ion in salt solution A is 1.5 mol / L; the molar ratio of nickel ion, cobalt ion and manganese ion in salt solution B is 60:20:20, and the sum of the molar concentrations of nickel ion, cobalt ion and manganese ion in salt solution B is 1.5 mol / L;

[0043] (2) preparing a precipitant sodium hydroxide solution and a complexing agent ammonia water respectively, wherein the concentration of the sodium hydroxide aqueous solution is 5 mol / L, and the concentration of the ammonia aqueous solution is 10 g / L;

[0044] (3) A reactor filled with deionized water was heated with a thermostatic water tank to make the temperature of the solution in the reactor reach 60°C and kept constant, 100L of salt solution A was added to the reactor filled with deionized water at a rate of 50mL / min, and 100L of salt solution B was added to salt solution A at a rate of 25mL / min. At the same time, sodium hydroxide aqueous solution and ammonia aqueous solution were added to the reactor at a rate of 25mL / min and 3mL / min, respectively, for coprecipitation reaction; nitrogen gas was introduced as protective gas, and the flow rate of the sodium hydroxide aqueous solution was adjusted to control the pH value of the reaction solution to 11.2, the concentration of ammonia in the solution to 3.0g / L, the stirring rate to 800r / min, and the nitrogen flow rate to 0.2m 3 / h, react under this condition for 75h, and finally obtain nickel cobalt manganese hydroxide precipitate;

[0045] (4) The obtained nickel-cobalt-manganese hydroxide precipitate was washed twice with hot alkali solution at a temperature of 70° C., then washed five times with deionized water, and dried at a temperature of 120° C. for 15 h to obtain a hydroxide precursor. The element distribution of the cross section of the hydroxide precursor was tested by EPMA. Figure 2 .

[0046] (5) The hydroxide precursor and lithium hydroxide are mixed evenly at a molar ratio of 1:1.08 and then sintered in a muffle furnace in two stages, and sufficient oxygen atmosphere is maintained during the sintering process. The two-stage sintering includes: heating from room temperature to 500°C at a heating rate of 2°C / min, keeping the temperature for 2 hours, then heating to 600°C at a heating rate of 2°C / min and keeping the temperature for 6 hours, then heating to 800°C at a heating rate of 2°C / min and keeping the temperature for 12 hours, then stopping heating and cooling to room temperature with the furnace; then heating to 300°C at a heating rate of 2°C / min and keeping the temperature for 10 hours, finally stopping heating and cooling to room temperature with the furnace, and obtaining a hollow porous concentration gradient positive electrode material.

[0047] Example 3

[0048] The method for preparing the hollow porous concentration gradient positive electrode material described in Example 3 comprises the following steps:

[0049] (1) preparing sulfate solution A and sulfate solution B, wherein the molar ratio of nickel ion, cobalt ion and manganese ion in salt solution A is 90:5:5, and the sum of the molar concentrations of nickel ion, cobalt ion and manganese ion in salt solution A is 1.3 mol / L; the molar ratio of nickel ion, cobalt ion and manganese ion in salt solution B is 60:20:20, and the sum of the molar concentrations of nickel ion, cobalt ion and manganese ion in salt solution B is 1.5 mol / L;

[0050] (2) preparing a precipitant sodium hydroxide solution and a complexing agent ammonia water respectively, wherein the concentration of the sodium hydroxide aqueous solution is 5 mol / L, and the concentration of the ammonia aqueous solution is 10 g / L;

[0051] (3) A reactor filled with deionized water was heated with a thermostatic water tank to make the temperature of the solution in the reactor reach 70°C and kept constant, 100L of salt solution A was added to the reactor filled with deionized water at a rate of 50mL / min, and 100L of salt solution B was added to salt solution A at a rate of 25mL / min, and sodium hydroxide aqueous solution and ammonia aqueous solution were added to the reactor at a rate of 20mL / min and 4mL / min, respectively, for coprecipitation reaction; nitrogen gas was introduced as protective gas, and the flow rate of the sodium hydroxide aqueous solution was adjusted to control the pH value of the reaction solution to 10.8, the concentration of ammonia in the solution to 3.0g / L, the stirring rate to 1000r / min, and the nitrogen flow rate to 0.3m 3 / h, react under this condition for 80h, and finally obtain nickel cobalt manganese hydroxide precipitate;

[0052] (4) The obtained nickel cobalt manganese hydroxide precipitate was rinsed twice with hot alkali solution at a temperature of 70° C., then washed 5 times with deionized water, and dried at a temperature of 120° C. for 15 h to obtain a hydroxide precursor;

[0053] (5) The hydroxide precursor and lithium hydroxide are mixed evenly at a molar ratio of 1:1.12 and then sintered in a muffle furnace in two stages, and sufficient oxygen atmosphere is maintained during the sintering process. The two-stage sintering includes: heating from room temperature to 500°C at a heating rate of 2°C / min, keeping the temperature for 2 hours, then heating to 600°C at a heating rate of 2°C / min and keeping the temperature for 6 hours, then heating to 800°C at a heating rate of 2°C / min and keeping the temperature for 12 hours, then stopping heating and cooling to room temperature with the furnace; then heating to 300°C at a heating rate of 2°C / min and keeping the temperature for 10 hours, finally stopping heating and cooling to room temperature with the furnace, and obtaining a hollow porous concentration gradient positive electrode material.

[0054] Example 4

[0055] The method for preparing the hollow porous concentration gradient positive electrode material described in Example 4 comprises the following steps:

[0056] (1) preparing nitrate solution A and nitrate solution B, wherein the molar ratio of nickel ion, cobalt ion and manganese ion in salt solution A is 100:0:0, and the sum of the molar concentrations of nickel ion, cobalt ion and manganese ion in salt solution A is 1.5 mol / L; the molar ratio of nickel ion, cobalt ion and manganese ion in salt solution B is 70:15:15, and the sum of the molar concentrations of nickel ion, cobalt ion and manganese ion in salt solution B is 1.5 mol / L;

[0057] (2) preparing a precipitant sodium hydroxide solution and a complexing agent ammonia water respectively, wherein the concentration of the sodium hydroxide aqueous solution is 5 mol / L, and the concentration of the ammonia aqueous solution is 10 g / L;

[0058] (3) A reactor filled with deionized water was heated with a thermostatic water tank to make the temperature of the solution in the reactor reach 65°C and kept constant, 100L of salt solution A was added to the reactor filled with deionized water at a rate of 50mL / min, and 100L of salt solution B was added to salt solution A at a rate of 25mL / min, and sodium hydroxide aqueous solution and ammonia aqueous solution were added to the reactor at a rate of 15mL / min and 5mL / min, respectively, for coprecipitation reaction; nitrogen gas was introduced as protective gas, and the flow rate of the sodium hydroxide aqueous solution was adjusted to control the pH value of the reaction solution to 10.9, the concentration of ammonia in the solution to 3.0g / L, the stirring rate was 1000r / min, and the nitrogen flow rate was 0.3m 3 / h, react under this condition for 80h, and finally obtain nickel cobalt manganese hydroxide precipitate;

[0059] (4) The obtained nickel cobalt manganese hydroxide precipitate was rinsed twice with hot alkali solution at a temperature of 70° C., then washed four times with deionized water, and dried at a temperature of 120° C. for 15 h to obtain a hydroxide precursor;

[0060] (5) The hydroxide precursor and lithium hydroxide are mixed evenly at a molar ratio of 1:1.16 and then sintered in a muffle furnace in two stages, and sufficient oxygen atmosphere is maintained during the sintering process. The two-stage sintering includes: heating from room temperature to 500°C at a heating rate of 2°C / min, keeping the temperature for 2 hours, then heating to 600°C at a heating rate of 2°C / min and keeping the temperature for 6 hours, then heating to 800°C at a heating rate of 2°C / min and keeping the temperature for 12 hours, then stopping heating and cooling to room temperature with the furnace; then heating to 300°C at a heating rate of 2°C / min and keeping the temperature for 10 hours, finally stopping heating and cooling to room temperature with the furnace, and obtaining a hollow porous concentration gradient positive electrode material.

[0061] Example 5

[0062] The method for preparing the hollow porous concentration gradient positive electrode material described in Example 5 comprises the following steps:

[0063] (1) preparing nitrate solution A and nitrate solution B, wherein the molar ratio of nickel ion, cobalt ion and manganese ion in salt solution A is 100:0:0, and the sum of the molar concentrations of nickel ion, cobalt ion and manganese ion in salt solution A is 1.8 mol / L; the molar ratio of nickel ion, cobalt ion and manganese ion in salt solution B is 60:20:20, and the sum of the molar concentrations of nickel ion, cobalt ion and manganese ion in salt solution B is 1.8 mol / L;

[0064] (2) preparing a precipitant sodium hydroxide solution and a complexing agent ammonia water respectively, wherein the concentration of the sodium hydroxide aqueous solution is 5 mol / L, and the concentration of the ammonia aqueous solution is 10 g / L;

[0065] (3) A reactor filled with deionized water was heated with a thermostatic water tank to make the temperature of the solution in the reactor reach 65°C and kept constant, 100L of salt solution A was added to the reactor filled with deionized water at a rate of 50mL / min, and 100L of salt solution B was added to salt solution A at a rate of 25mL / min, and sodium hydroxide aqueous solution and ammonia aqueous solution were added to the reactor at a rate of 10mL / min and 6mL / min, respectively, for coprecipitation reaction; nitrogen gas was introduced as protective gas, and the flow rate of the sodium hydroxide aqueous solution was adjusted to control the pH value of the reaction solution to 10.9, the concentration of ammonia in the solution to 3.0g / L, the stirring rate to 1000r / min, and the nitrogen flow rate to 0.3m 3 / h, react under this condition for 80h, and finally obtain nickel cobalt manganese hydroxide precipitate;

[0066] (4) The obtained nickel cobalt manganese hydroxide precipitate was rinsed twice with hot alkali solution at a temperature of 70° C., then washed four times with deionized water, and dried at a temperature of 120° C. for 15 h to obtain a hydroxide precursor;

[0067] (5) The hydroxide precursor and lithium hydroxide are mixed evenly in a molar ratio of 1:1.2 and then sintered in a muffle furnace in two stages, and sufficient oxygen atmosphere is maintained during the sintering process. The two-stage sintering includes: heating from room temperature to 500°C at a heating rate of 2°C / min, keeping the temperature for 2 hours, then heating to 600°C at a heating rate of 2°C / min and keeping the temperature for 6 hours, then heating to 800°C at a heating rate of 2°C / min and keeping the temperature for 12 hours, then stopping heating and cooling to room temperature with the furnace; then heating to 300°C at a heating rate of 2°C / min and keeping the temperature for 10 hours, finally stopping heating and cooling to room temperature with the furnace, and obtaining a hollow porous concentration gradient positive electrode material.

[0068] Comparative Example 1

[0069] (1) preparing a sulfate solution C, wherein the molar ratio of nickel ions, cobalt ions, and manganese ions in the sulfate solution C is 80:10:10, and the sum of the molar concentrations of nickel ions, cobalt ions, and manganese ions in the sulfate solution C is 1.3 mol / L;

[0070] (2) preparing a precipitant sodium hydroxide solution and a complexing agent ammonia water respectively, wherein the concentration of the sodium hydroxide aqueous solution is 5 mol / L, and the concentration of the ammonia aqueous solution is 10 g / L;

[0071] (3) A thermostatic water tank was used to heat the reactor filled with deionized water, so that the temperature of the solution in the reactor reached 65°C and was kept constant. 100L of salt solution C was added to the reactor filled with deionized water at a rate of 50mL / min. At the same time, sodium hydroxide aqueous solution and ammonia aqueous solution were added to the reactor at a rate of 30mL / min and 2mL / min, respectively, for coprecipitation reaction. Nitrogen was introduced as a protective gas, and the flow rate of the sodium hydroxide aqueous solution was adjusted to control the pH value of the reaction solution to 10.9, the concentration of ammonia in the solution to 3.0g / L, the stirring rate to 1000r / min, and the nitrogen flow rate to 0.3m 3 / h, react under this condition for 80h, and finally obtain nickel cobalt manganese hydroxide precipitate;

[0072] (4) The obtained nickel cobalt manganese hydroxide precipitate was rinsed twice with hot alkali solution at a temperature of 70° C., then washed four times with deionized water, and dried at a temperature of 120° C. for 15 h to obtain a hydroxide precursor;

[0073] (5) The hydroxide precursor and lithium hydroxide are mixed evenly at a molar ratio of 1:1.04 and then sintered in a muffle furnace in two stages, and sufficient oxygen atmosphere is maintained during the sintering process. The two-stage sintering includes: heating from room temperature to 500°C at a heating rate of 2°C / min, keeping the temperature for 2 hours, then heating to 600°C at a heating rate of 2°C / min and keeping the temperature for 6 hours, then heating to 800°C at a heating rate of 2°C / min and keeping the temperature for 12 hours, then stopping heating and cooling to room temperature with the furnace; then heating to 300°C at a heating rate of 2°C / min and keeping the temperature for 10 hours, finally stopping heating and cooling to room temperature with the furnace, and obtaining a dense non-concentration gradient positive electrode material.

[0074] Comparative Example 2

[0075] (1) Sulfate solution A and sulfate solution B are prepared, wherein the molar ratio of nickel ion, cobalt ion and manganese ion in salt solution A is 90:5:5, and the sum of the molar concentrations of nickel ion, cobalt ion and manganese ion in salt solution A is 1.3 mol / L; the molar ratio of nickel ion, cobalt ion and manganese ion in salt solution B is 60:20:20, and the sum of the molar concentrations of nickel ion, cobalt ion and manganese ion in salt solution B is 1.3 mol / L.

[0076] (2) preparing a precipitant sodium hydroxide solution and a complexing agent ammonia water respectively, wherein the concentration of the sodium hydroxide aqueous solution is 5 mol / L, and the concentration of the ammonia aqueous solution is 10 g / L;

[0077] (3) A reactor filled with deionized water was heated with a thermostatic water tank to make the temperature of the solution in the reactor reach 65°C and kept constant, 100L of salt solution A was added to the reactor filled with deionized water at a rate of 50mL / min, and 100L of salt solution B was added to salt solution A at a rate of 25mL / min, and sodium hydroxide aqueous solution and ammonia aqueous solution were added to the reactor at a rate of 25mL / min and 3mL / min, respectively, for coprecipitation reaction; nitrogen gas was introduced as protective gas, and the flow rate of the sodium hydroxide aqueous solution was adjusted to control the pH value of the reaction solution to 10.9, the concentration of ammonia in the solution to 3.0g / L, the stirring rate was 1000r / min, and the nitrogen flow rate was 0.3m 3 / h, react under this condition for 80h, and finally obtain nickel cobalt manganese hydroxide precipitate;

[0078] (4) The obtained nickel cobalt manganese hydroxide precipitate was rinsed twice with hot alkali solution at a temperature of 70° C., then washed four times with deionized water, and dried at a temperature of 120° C. for 15 h to obtain a hydroxide precursor;

[0079] (5) The hydroxide precursor and lithium hydroxide are mixed evenly at a molar ratio of 1:1.04 and then sintered in a muffle furnace, and sufficient oxygen atmosphere is maintained during the sintering process. The sintering process includes: heating from room temperature to 800°C at a heating rate of 2°C / min, keeping the temperature for 20 hours, and finally stopping heating and cooling to room temperature with the furnace to obtain a dense non-concentration gradient material positive electrode material.

[0080] from Figure 3-7 It can be seen that a large void appears in the center of the positive electrode material obtained after sintering. This is because the nickel content in the center of the precursor is high, which makes the whiskers in the center relatively loose. In addition, during the high-temperature sintering process, metal elements with high concentrations will diffuse to metal elements with low concentrations. This structure shortens the diffusion distance of Li ions and can also effectively slow down the volume expansion and contraction caused by repeated Li ion insertion and extraction.

[0081] Study on the performance of the positive electrode material of the present invention

[0082] The positive electrode material and acetylene black prepared above are dispersed in a NMP solution containing PVDF at a mass ratio of 98:2, and stirred evenly to obtain a slurry. The slurry is evenly coated on a 15μm thick aluminum foil, vacuum dried at 110°C for 4h, and then pressed into a circular electrode sheet with a diameter of 15mm using a tablet press. In a glove box, the positive electrode shell, positive electrode sheet, electrolyte, diaphragm, lithium sheet, electrolyte, nickel foam, and negative electrode shell are assembled and sealed to obtain a button battery. Among them, the electrolyte is a 1mol / L LiPF6 solution (the solvent includes EC and DMC in a volume ratio of 1:1); the diaphragm is a PE film.

[0083] The button cell was subjected to constant current charge and discharge test and rate test, with the test voltage range being 3.0V-5.0V.

[0084] The results are shown in Table 1:

[0085] Table 1 Capacity and 300 cycle capacity retention rate of the positive electrode material of the present invention

[0086]

[0087] As can be seen from Table 1, the discharge specific capacity at 0.2C rate has reached a high level, up to 199.8mAh / g. The capacity retention rate of 300 charge and discharge cycles at 50°C has been significantly improved compared with ordinary high-nickel positive electrode materials, up to 93.6%. It can be seen that this kind of internal hollow porous concentration gradient positive electrode material can improve the material's cycle performance.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A hollow porous concentration gradient positive electrode material, characterized in that: The concentrations of nickel ions, cobalt ions and manganese ions contained in the positive electrode material are distributed in a gradient from the center to the surface. The concentration gradient of nickel ions contained in the positive electrode material decreases from the center to the surface of the positive electrode material. The concentration of nickel ions at the center of the positive electrode material is 90%-100%, and the concentration of nickel ions at the surface of the positive electrode material is 60%-70%. The concentration gradients of cobalt ions and manganese ions contained in the positive electrode material increase from the center to the surface of the positive electrode material. The concentrations of cobalt ions and manganese ions at the center of the positive electrode material are 0%-5%, and the concentrations of cobalt ions and manganese ions at the surface of the positive electrode material are 15%-20%. The positive electrode material is a polycrystalline material; The method for preparing the positive electrode material comprises the following steps: (1) preparing a metal salt solution: preparing a salt solution A containing nickel, and / or cobalt, and / or manganese metal ions, wherein the molar ratio of nickel ion, cobalt ion, and manganese ion is (100-90):(0-5):(0-5); preparing a salt solution B containing nickel, cobalt, and manganese metal ions, wherein the molar ratio of nickel ion, cobalt ion, and manganese ion is (60-70):(20-15):(20-15); (2) preparing a precipitant solution and a complexing agent solution; (3) passing the solution B described in step (1) into solution A, and then passing the mixture of solution B and solution A into a reactor filled with deionized water, and at the same time passing a precipitant solution and a complexing agent solution into the reactor, and performing a coprecipitation reaction under inert conditions to obtain a nickel cobalt manganese hydroxide precipitate; the rate at which the mixture of solution B and solution A is passed into the reactor is twice the rate at which solution B is passed into solution A; (4) The nickel cobalt manganese hydroxide precipitate obtained in step (3) is washed and dried in sequence to obtain a hydroxide precursor, which is then mixed evenly with a lithium salt and sintered to obtain a hollow porous concentration gradient positive electrode material; the sintering is as follows: first, the temperature is increased to 500°C at a heating rate of 1 to 10°C / min, and the temperature is kept at this temperature for 2 to 10 hours; then, the temperature is increased to 600°C at a heating rate of 1 to 10°C / min, and the temperature is kept at this temperature for 1 to 2 hours; then, the temperature is increased to 800°C at a heating rate of 1 to 10°C / min, and the temperature is kept at this temperature for 1 to 20 hours, and then, the temperature is cooled to room temperature in the furnace; then, the temperature is increased to 300°C at a heating rate of 1 to 10°C / min, and the temperature is kept at this temperature for 1 to 15 hours, and finally, the temperature is cooled to room temperature in the furnace to obtain a hollow porous concentration gradient positive electrode material.

2. The hollow porous concentration gradient positive electrode material according to claim 1, characterized in that: The acid radical ions of the nickel ions, cobalt ions and manganese ions are sulfate ions, nitrate ions, acetate ions or chlorate ions.

3. The method for preparing the positive electrode material according to claim 1, characterized in that: The following steps are involved: (1) preparing a metal salt solution: preparing a salt solution A containing nickel, and / or cobalt, and / or manganese metal ions, wherein the molar ratio of nickel ion, cobalt ion, and manganese ion is (100-90):(0-5):(0-5); preparing a salt solution B containing nickel, cobalt, and manganese metal ions, wherein the molar ratio of nickel ion, cobalt ion, and manganese ion is (60-70):(20-15):(20-15); (2) preparing a precipitant solution and a complexing agent solution; (3) passing the solution B described in step (1) into solution A, and then passing the mixture of solution B and solution A into a reactor filled with deionized water, and at the same time passing a precipitant solution and a complexing agent solution into the reactor, and performing a coprecipitation reaction under inert conditions to obtain a nickel cobalt manganese hydroxide precipitate; the rate at which the mixture of solution B and solution A is passed into the reactor is twice the rate at which solution B is passed into solution A; (4) The nickel cobalt manganese hydroxide precipitate obtained in step (3) is washed and dried in sequence to obtain a hydroxide precursor, which is then mixed evenly with a lithium salt and sintered to obtain a hollow porous concentration gradient positive electrode material; the sintering is as follows: first, the temperature is increased to 500°C at a heating rate of 1 to 10°C / min, and the temperature is kept at this temperature for 2 to 10 hours; then, the temperature is increased to 600°C at a heating rate of 1 to 10°C / min, and the temperature is kept at this temperature for 1 to 2 hours; then, the temperature is increased to 800°C at a heating rate of 1 to 10°C / min, and the temperature is kept at this temperature for 1 to 20 hours, and then, the temperature is cooled to room temperature in the furnace; then, the temperature is increased to 300°C at a heating rate of 1 to 10°C / min, and the temperature is kept at this temperature for 1 to 15 hours, and finally, the temperature is cooled to room temperature in the furnace to obtain a hollow porous concentration gradient positive electrode material.

4. The method for preparing the positive electrode material according to claim 3, characterized in that: In step (1), the sum of the molar concentrations of metal ions in salt solution A and salt solution B is 1.3 mol / L-1.8 mol / L; and the acid ions in salt solution A and salt solution B are sulfate ions, nitrate ions, acetate ions or chlorate ions.

5. The method for preparing the positive electrode material according to claim 3, characterized in that: The concentration of the precipitant is 5 mol / L, and the precipitant is NaOH, KOH, Na2CO3, NaHCO3, K2CO3 or KHCO3; the concentration of the complexing agent is 10 g / L, and the complexing agent is ammonia water, ammonium bicarbonate, ammonium carbonate or ammonium oxalate.

6. The method for preparing the positive electrode material according to claim 3, characterized in that: The rate at which solution B is passed into solution A is 10-50 mL / min, the rate at which the mixed solution of solution B and solution A is passed into the reactor is 20-100 mL / min, the rate at which the precipitant solution is passed into the reactor is 5-30 mL / min, and the rate at which the complexing agent solution is passed into the reactor is 1-10 mL / min.

7. The method for preparing the positive electrode material according to claim 3, characterized in that: In step (3), the inert condition is to fill the reactor with inert gas nitrogen; the temperature of the coprecipitation reaction is 20-70°C, the pH is 7.0-11.0, the stirring speed is 300-2000r / min, and the reaction time under these conditions is 20-100h.

8. The method for preparing the positive electrode material according to claim 3, characterized in that: In step (4), the cleaning is: firstly rinse with alkaline solution at a temperature of 50-90°C, and then rinse with deionized water.

9. The method for preparing the positive electrode material according to claim 3, characterized in that: In step (4), the lithium salt is at least one of lithium hydroxide, lithium carbonate, lithium nitrate and lithium acetate, and the molar ratio of the hydroxide precursor to the lithium salt is 1:1-1.2.